Predicting first attendance at psychiatry appointments in patients with dissociative seizures. (January 2020) - Stone, Jon; Callaghan, Hannah; Robinson, Emily J.; Carson, Alan; Reuber, Markus; Chalder, Trudie; Perdue, Iain; Goldstein, Laura H.
Graphical abstract: Highlights: ∼20 % neurology dissociative seizure patients referred to psychiatry didn't attend. Demographic, seizure variables and patient diagnostic confidence weren't predictive. "Having a carer" was the only variable associated with attendance. Neurologists shouldn't use demographic data to predict attendance at psychiatry. Abstract: Purpose: Patients with dissociative (non-epileptic) seizures typically receive their diagnosis from neurologists, but are often referred to psychiatrists, whom they may be reluctant to go and see. We aimed to assess which factors were associated with first attendance at psychiatric services. Methods: A cohort study of 698 participants involved in the pre-randomisation phase of the CODES trial, a randomised controlled trial assessing the benefit of cognitive behavioural therapy for dissociative seizures when added to standardised medical (including psychiatric) care. Patients diagnosed by neurologists from 27 UK centres provided demographic information and a measure of diagnostic confidence. Neurologists described predominant seizure type and comorbidity with epilepsy. We analysed hypothesised (young age, male, residing in areas of higher deprivation, low belief in diagnosis) and exploratory factors for their association with first attendance with the psychiatrist about 3 months later. Results: 568/698 (81.4 %) participants attended a psychiatry appointment. None of the following were associated with attendance: Location, age, gender, deprivation score, relationship status, ethnicity, level of education, employment status, receipt of disability benefits, duration, previous diagnosis of epilepsy or mental health problems and degree of confidence in the diagnosis. The only variable differing between groups was having a carer (21.5 % not attending vs 38.6 % attending). Conclusion: First attendance at a psychiatry appointment after a neurologist had given a diagnosis of dissociative seizures was not associated with any hypothesised predictors, including patient confidence in the diagnosis. Neurologists should put aside any expectations about these variables when referring to and anticipating attendance with a psychiatrist.